2006
DOI: 10.4049/jimmunol.177.8.5631
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-10 Suppressors in Lung Transplant Patients by CD4+25+ Regulatory T Cells through CTLA-4 Signaling

Abstract: T cell-mediated autoimmunity to collagen V (col-V), a sequestered yet immunogenic self-protein, can induce chronic lung allograft rejection in rodent models. In this study we characterized the role of CD4+CD25+ regulatory T cells (Tregs) in regulating col-V autoimmunity in human lung transplant (LT) recipients. LT recipients revealed a high frequency of col-V-reactive, IL-10-producing CD4+ T cells (TIL-10 cells) with low IL-2-, IFN-γ-, IL-5-, and no IL-4-producing T cells. These TIL-10 cells were distinct from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 49 publications
3
64
0
Order By: Relevance
“…We have shown that BOS+ patients develop early post-transplant inflammation which may activate allo-as well as auto-immunity (18). Further, loss of regulatory T cells which down regulate both auto as well as alloimmunity, may lead to increased immune response leading to the immunopathogenesis of BOS (19). Our finding that sCD30 levels are elevated several months prior to clinical onset of BOS strongly suggests activation of the immune response leading to an increase in the serum sCD30 levels.…”
Section: Discussionmentioning
confidence: 52%
“…We have shown that BOS+ patients develop early post-transplant inflammation which may activate allo-as well as auto-immunity (18). Further, loss of regulatory T cells which down regulate both auto as well as alloimmunity, may lead to increased immune response leading to the immunopathogenesis of BOS (19). Our finding that sCD30 levels are elevated several months prior to clinical onset of BOS strongly suggests activation of the immune response leading to an increase in the serum sCD30 levels.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, we must consider the unique collaboration that exists between human memory Th-17 cells and CD14 1 macrophages as a possible link between adaptive and innate immunity. Bharat and colleagues, using PBMCs from patients who had received a lung transplant, demonstrated a key role for immune regulation by CD4 1 CD25 1 T-regulatory cells in preventing outgrowth of col(V)-reactive Th-1 (IFN-g) effector cells in long-term cultures (31,32). However, this report did not address the mechanisms of T-effector function in vivo or the role of IL-17.…”
Section: Discussionmentioning
confidence: 78%
“…As shown, grafts from hAAT-treated mice ( Fig. 4A, representative day 72) exhibit a significantly elevated expression of foxp3, TGF-␤, and cytotoxic T lymphocyte antigen-4 (CTLA-4), representing the expected phenotype of Treg cells (17)(18)(19)(20). In contrast, the expression of these genes was either below detection or terminated early in grafts from albumin-treated mice (days 1, 3, 5, and 7).…”
Section: Prolonged Administration Of Haat To Diabetic Islet Allograftmentioning
confidence: 90%